KAJIAN PROGRAM KEGIATAN PENYEDIAAN DAN REHABILITASI SARANA DAN PRASARANA PRODUKSI PERIKANAN TANGKAP TERHADAP PENINGKATAN PENDAPATAN NELAYAN DI KABUPATEN TANAH LAUT KALIMANTAN SELATAN - Saprani Saprani; Idiannor Mahyudin; Erma Agusliani (EnviroScienteae, 2016)
This research aimed to (1) evaluate and analyze the implication of the providing and rehabilitation program of the production facilities and infrastructures for the fishery to the socio-economic performance of the fishing community in Tanah Laut Regency according to institutional after receiving program package; and (2) compare and analyze the fishermen income level before and after receiving the package of the providing and rehabilitation program of the production facilities and infrastructures for the fishery.    This research was carried out in Tanah Laut Regency, South Kalimantan, with the objects of receivers of the providing and rehabilitation program of the production facilities and infrastructures for the fishery who joined the Fishermen Joint Business Group. The collected data were the data that were directly originated from results of observation in the location of the research, and the other supporting data was related to the object of the research.    Results of the research showed that the providing and rehabilitation program of the production facilities and infrastructures for the fishery, which requiring the fishing community to form a business institutional of fishermen, showed the positive effect of the socio-economic condition of the fishing community in Tanah Laut Regency, in form of (1) change in the fishing social status from workers to vessel owners; (2) improvement of knowledge and technical capability of fishing from the knowledge gained autodidactic to the knowledge acquired through the training organized by builder institution, both central and local government; and (3) economically, the fishermen acquired income improvement through the implementation of a system for reasonable production sharing which was dealt by the collective agreement in the fishermen institutional. The fishermen income level after receiving the package of the providing and rehabilitation program of the production facilities and infrastructures for the fishery had increased very significantly, as shown by the increase in income between 42 - 290%, or an average of 136%, from prior to receiving the program package.